Analysis of Midwife Performance, Family Support, and Health Facilities on Antenatal Care Visits - Sulistina Dewiyanti; Yenny Puspitasari; Prima Dewi Kusumawati (KHD Production, 2026)
Antenatal care (ANC) utilization is a key indicator of maternal health outcomes; however, coverage remains suboptimal, with many pregnant women failing to meet recommended visit standards. This study aimed to examine the influence of midwives' performance, family support, and the availability of health facilities on compliance with ANC visits among pregnant women. A quantitative, observational, cross-sectional study was conducted involving 147 pregnant women selected by simple random sampling. Data were obtained from medical records and structured questionnaires and analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) techniques. The results demonstrated that midwives' performance was significantly associated with ANC visit completeness (χ² = 228.766; p < 0.001). Similarly, family support (χ²=208.597; p<0.001) and the availability of health facilities (χ²=164.881; p<0.001) were significantly associated with ANC compliance. Multivariate analysis confirmed that these factors were significant predictors of ANC utilization. midwives' performance, family support, and the availability of health facilities all play critical roles in improving compliance with ANC visits. Strengthening healthcare provider performance, enhancing family involvement, and ensuring adequate health service infrastructure are essential strategies to increase ANC coverage and improve maternal health outcomes.